Online licensing system for pharmaceutical service division, ministry of health / Subashini Ramakrishnan - Subashini, Ramakrishnan (2002)
Internet has often been referred to as the 'Information Superhighway'.The concept of being able to access information quickly and easily led to the vision of the Internet. It provides, uses or makes accessible, either publicly or privately; high level services layered on the communications and related infrastructure. With the advancement of information technology and increasing number of users getting connected to the Internet, various techniques are being employed on the World Wide Web (WWW). It provides sustaining facility accessible to hundreds of million of people worldwide. Therefore, the Online Licensing System is expected to provide value-added services (pharmacists, wholesalers, manufacturers and importers of medicines) and at the same time enhancing the features of current state of their existing web page. Furthermore, at current situation, there is no such existing online web-based licensing system being used in Malaysia. The Online Licensing System for Pharmacy Division, Ministry of Health (MOH) will focus on resolving the drawbacks of the conventional manual licensing process. In overall, this web-based online application will help to automate the licensing process in a more systematic and easier way.